Screening Polimer Untuk Eor (Enhanced Oil Recovery) Di Lapangan “X” Minyak Cekungan Sumatera Tengah - Septiana, Dwi; Helwani, Zuchra; Abdurrahman, Muslim (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2022)
Oil is the energy source that people demand and use the most right now. Recent years have seen a lot of interest in polymer flooding as a cutting-edge chemical-based enhanced oil recovery (EOR) solution. Field X Minyak Cekungan Sumatera is acceptable for chemical EOR (Polymer) testing with a success range of up to 70%. The polymer solution will follow the channel that the water has created, and because of its high viscosity, it tends to